ANALISIS PUTUSAN HAKIM TERHADAP ANAK PELAKU TINDAK PIDANA KEJAHATAN SEKSUAL (Studi Putusan Pengadilan Wonogiri Nomor : 4/Pid.Sus-Anak/2018/Pn Wng) - WARDHANA, SINDRA RIEFLY (Dinamika Hukum, 2019)
The purpose of this study is what is the basis for the judge's judgment in issuing a criminal court decision (No.: 4 / Pid.Sus-Anak / 2018 / Pn Wng) and whether a criminal decision handed down in a case (No. 4 / Pid.Sus-Anak / 2018 / Pn Wng) by the Judge is in accordance with UURI provision No. 11 of 2012 concerning the Juvenile Justice System. The method of approach in this paper is empirical juridical. This research method uses descriptive normative. Data sources using primary and secondary data and tertiary data. Data collection techniques using interview studies and literature studies. To analyze the data, researchers used the Qualitative Data Analysis method. Based on the results of this study indicate that: 1). Legal considerations of judges in passing verdicts (No. 4 / Pid.sus.anak / 2018 / PN.Wng), have a mistake because the judge in considering the case only handed down a criminal code in accordance with Article 81 paragraph (2) of the Child Protection Act, without include article 64 paragraph (1) of the Criminal Code concerning continuing actions. The facts that occurred in the field, the actions of the defendant who committed the crime of sexual intercourse against the victim were carried out repeatedly, which is 5 times and should be included in one of the incriminating matters. 2). Judges' decisions analyzed by the author, have problems where the decision is not in accordance with the SPPA law. One of the points in the decision was that the judge decided on a criminal act in the form of treatment and or rehabilitation at the foundation for the development of bad boys (YPAN) Bhina Putera Surakarta for 2 (two) years and a criminal fine of Rp.60,000,000.00 (sixty million rupiah) and with the provision that if the fine is not paid, then it is obligatory to replace it with work training for 1 (one) month if in the material law the cumulative penalty is imposed in the form of prison and the fine is replaced with work training.